Staro- i średniopolskie nazwy ciast - Zuzanna Krótki (Annales Universitatis Paedagogicae Cracoviensis. Studia Linguistica, 2016)
n the article herein the thirty-four lexical units were undertaken and analysed thorough- ly which maintained the old- and middle-Polish appellations of baking products – pastries. Stemming from the etymology, the motivation was investigated, the meaning and the semantic changes in the gathered texts of words were also scrutinized and put under the magnifying glass. It was evidenced that the nomination of investigated names of ‘baked cakes’ consisted of six general functions such as: 1. literal character of particular cake; 2. indication of its main baking ingredients; 3. the form of it; 4. origin of a cake; 5. increase of ‘favourable of a cake’ by a referral to the authority; 6. correlation of the particular cake with its rites and holidays (during which the pastries were served) (sic!). Most frequently the old names of ‘baked good- ies’ were made as simple associations and were coupled with particular shape of the bake.